Regulatory Response of Methanococcus maripaludis to Alanine, an Intermediate Nitrogen Source - Lie, Thomas J. (American Society for Microbiology, 2002)
In the methanogenic archaeon Methanococcus maripaludis, growth with ammonia results in conditions of nitrogen excess. Complete repression of nitrogen fixation (nif) gene transcription occurs, and glutamine synthetase (glnA) gene transcription falls to a basal constitutive level. In addition, ammonia completely switches off nitrogenase enzyme activity. In contrast, growth with dinitrogen as the sole nitrogen source results in nitrogen starvation, full expression of nif and glnA, and high activity of nitrogenase. Here we report that a third nitrogen source, alanine, results in an intermediate regulatory response. Growth with alanine resulted in intermediate transcription of nif and glnA, and addition of alanine to a nitrogen-fixing (diazotrophic) culture caused partial switch-off of nitrogenase. This uniformity of response occurred despite differences in regulatory mechanisms. Nitrogenase switch-off requires the nitrogen sensor homologs NifI(1) and NifI(2), while transcriptional regulation of nif and glnA relies on a different, unknown sensor mechanism. In addition, although nif and glnA transcription are governed by a common repressor, the numbers and arrangements of repressor binding sites differ. Thus, the nif promoter region contains two operators situated downstream of the transcription start site, while the glnA promoter region contains only one operator just upstream of two closely spaced transcription start sites. In a previous study of nif expression using ammonia, we were able to detect a role only for the first nif operator in repression. Here we show that nif repression by alanine requires the second operator as well. In contrast, in the case of glnA the single operator was sufficient for repression by ammonia or alanine. These results suggest a uniform cellular response to nitrogen that is mediated by a different mechanism in each case.